Використання лужного прискорювача на основі алюмінату натрію в технології бетону - Камінський, А. Т.; Kaminskyy, A. T. (Видавництво Львівської політехніки, 2019)
Розглянуто використання лужних прискорювачів тверднення у будівництві. Досліджено вплив лужного прискорювача тверднення на основі алюмінату натрію (ЛА) на фізико-механічні властивості дрібнозернистих бетонів. Методом математичного планування експерименту встановлено, що оптимальний вміст алюмінату натрію (1,5 мас. %) та суперпластифікатора полікарбоксилатного типу ПКС (1,0 мас. %) забезпечує одержання бетону на основі композиційного портландцементу ПЦ ІІ/Б-К(Ш- П-В)-400Р-Н з високою ранньою міцністю. Методом рентгенофазового аналізу досліджено продукти взаємодії в системі Са(ОН)2-ЛА – СаSO4 .2H2O і встановлено наявність інтенсивних рефлексів етрингіту. Показано, що введенням прискорювача на основі алюмінату натрію до складу бетонів можна прискорити їх тверднення та підвищити ранню міцність, а з використанням композиційного цементу – покращити експлуатаційні властивості. Показано, що лужний прискорювач на основі алюмінату натрію створює можливості одержання безусадкових бетонів і розчинів для торкретування, а також швидкого виконання ремонтних і відновлювальних робіт.

The article considers the use of alkaline accelerators of hardening in the construction industry. The influence of alkaline accelerator on the basis of sodium aluminate on the physical and mechanical properties of fine-grained concrete has been investigated. It has been shown that the including of alkali accelerator of hardening Na [Al (OH)4] leads to an increase in water consumption and reducing the strength of the binding agent in the all terms of hardening. The method of mathematical planning of the experiment determined that an optimum content of 1.5 mas.% of aluminum-containing alkaline accelerator and 1 mas.% superplasticizer of polycarboxylate type PCЕ ensures the production of fine-grained concrete with high early strength. Due to experimental researches was determined that optimal content of Na [Al (OH)4] – 1.5 % and PCЕ – 1 % provides the production of modified concrete with high early strength – after 1 day flexural strength – 4.7 MPa, compressive strength – 15,9 MPa. It has been shown that the introduction of an accelerator based on aluminate and PCЕ leads to an acceleration of hydration for 5 hours and a decrease in temperature to 60 °C. It has been shown that the mechanism of action of sodium aluminate in the cemetery system consists in the rapid formation of the product of hydration of the ettringitе. The system of Ca(OH)2-Na [Al(OH)4] – CaSO4.2H2O was investigated by the method of X-ray diffraction analysis and it was determined the presence of intense reflexes of ettringitе. The introduction of an alkaline accelerator based on sodium aluminate into the composition of concrete allows them to accelerate their hardening and increase the early strength, and the use of composite cement – provides improved operational properties. Using of alkaline accelerator based on sodium aluminate in concrete technology creates the possibility of obtaining sprayed concrete and mortars for gunning, and also the rapid implementation of repair and renovation works.
The use of alkaline accelerator based on sodium aluminate in concrete technology
Keywords: лужний прискорювач; алюмінат натрію; композиційний портландцемент; полікарбоксилатний суперпластифікатор; alkaline accelerator; sodium aluminate; Portland composite cement; polycarboxylate superplasticizer; 666.972